Physical Impacts of Climate Change on Water Resources - Miralles-Wilhelm, Fernando (World Bank, Washington, DC, 2017)
Despite the well-recognized role of water in transmitting climate impacts to some of the growth drivers of the economy, the water sector has been largely ignored in climate change deliberations. The impacts are projected to vary regionally, and are likely to include changes in average hydroclimate patterns (precipitation, surface runoff, and stream flow), as well as increases in the probability of extreme events. Climate shocks are likely to impose higher costs than gradual changes in climate averages. Prudent management of water resources will be pivotal in addressing the climate challenge—both for adapting to the effects of climate change as well as for meeting global greenhouse gas mitigation goals. The precise consequences of climate change on the hydrological cycle are uncertain, which makes adaptation especially challenging. Uncertainty regarding impacts is partly a consequence of the limitations of climate models. Despite improvements in climate science, the Global Circulation Models developed to project climate futures generate a wide range of projections that often disagree on both the direction and magnitude of precipitation changes. Furthermore, these models have not been designed to predict changes in the hydrological cycle and lack the precision required for planning and managing water resources. In addition to this, changes in the hydrological cycle imply that future water systems may not resemble the past (non-stationarity), so historic trends as used in engineering designs, no longer serve as a reliable guide for assessing and managing future risks. This study presents an investigation of the impacts of climate change on water resources throughout the world, and specific effects on water dependent sectors of the economy such as urban, energy, and agriculture. The results can be used to illustrate the centrality of water in achieving global climate change goals.